Respostas
respondido por:
2
Ola!!
Resolução!!
PA ( 1, 3, ... )
a1 = 1. a2 = 3, ....
r = a2 - a1
r = 3 - 1
r = 2
an = a1 + ( n - 1 ) • r
an = 1 + ( n - 1 ) • 2
an = 1 + 2n - 2
an = - 1 + 2n
an = 2n - 1 → Termo geral
Espero ter ajudado!
Resolução!!
PA ( 1, 3, ... )
a1 = 1. a2 = 3, ....
r = a2 - a1
r = 3 - 1
r = 2
an = a1 + ( n - 1 ) • r
an = 1 + ( n - 1 ) • 2
an = 1 + 2n - 2
an = - 1 + 2n
an = 2n - 1 → Termo geral
Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás